Why Academic Software Should be Open Source - Paumier, Sébastien (Infotheca - Journal for Digital Humanities, 2024)
Everyone has heard about “free software” and “open source”, but what those terms actually mean is not always very clear, even for people that produce software. First of all, I will briefly explain those terms, and the reader will see that the open source philosophy has many ideas in common with Science. Then, I will define what I mean by “academic software” and I will present some arguments in order to show that Science would benefit a lot if scientists that produce software released them as open source.